Development of Multisensory Reading Card Media Based on QR Video to Overcome Letter Reversal in Grade III Students of SDN Sumur Welut III with Indications of Dyslexia - Putri Arina Hidayati; Neni Mariana (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Reading is a fundamental skill that is crucial for the academic success of elementary school students. One common obstacle experienced by third-grade students in Phase B at SDN Sumur Welut III is letter reversal, which is difficulty distinguishing between similar-looking letters like b–d and p–q. This is also often an early indicator in children with dyslexia. This obstacle not only disrupts reading fluency but also lowers students' self-confidence. This research aims to develop multisensory reading card media based on QR video as an innovative solution to help students overcome difficulties in reading similar letters related to dyslexia symptoms. The research method uses the Research and Development (R&D) model with a 4D approach, limited to the Develop stage, resulting in an initial prototype of the learning media. The developed media combines visual, auditory, and kinesthetic aspects thru the use of reading direction arrows, the selection of dyslexia-friendly fonts, and the integration of QR codes linked to word pronunciation videos. The development results show that this reading card has simple, practical, and adaptable characteristics for use both at school and at home. The novelty of this research lies in the integration of print media with simple technology, differing from previous studies that tended to focus solely on visual or fully digital aspects. Although it is still a prototype and has not been empirically tested, this medium has the potential to be an innovative alternative to support the improvement of basic literacy, particularly for students with reading difficulties, including indications of dyslexia. Further research is needed to test the validity, practicality, and effectiveness of the media in a broader learning context. Keywords: Literacy, Dyslexia, Multisensory, Cards, QR